Understanding the Mechanism of User Experience Role in Educational Livestreaming Platform - Zhao, Hong; Zhou, Yajun (Frontiers in Psychology, 2022)
The booming development of educational livestreaming platform has caused the prevalence of user experience to a certain extent, which profoundly affects users' purchase intention and be-havior, and has become a hot topic of current research in the online education field, yet there is a lack of in-depth analysis on the mechanism of the role of user experience in influencing purchase intention. Based on the analysis of user experience and psychological ownership, this study con-structs a moderated mediation model to investigate the mediating psychological mechanism and boundary conditions of user experience affecting purchase intention. In this study, a valid sample of 372 users was used for structural equation modeling analysis. The results of the study found that user experience not only had a significant positive effect on purchase intention, but was also mediated by psychological ownership. It was also found that the effect of psychological owner-ship on purchase intention was moderated by privacy concerns. This study examines the role of user experience on purchase intention and reveals the mechanism of the role of user experience in educational livestreaming platform.